1988
DOI: 10.1055/s-2007-999649
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Oral Nystatin and Fungal Infections in Very-Low-Birthweight Infants

Abstract: Prevention of systemic fungal infection in the very-low-birthweight infant is important since it is associated with a high morbidity and mortality. To determine if oral nystatin administration could prevent fungal colonization and infection, we evaluated 67 preterm infants with birthweights less than 1250 gm. Thirty-three infants received 1 ml (100,000 units/ml) of nystatin inside the mouth every 8 hours until 1 week after extubation. Oropharyngeal, rectal, blood, and urine cultures were obtained on the 1st da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 2 publications
8
72
1
1
Order By: Relevance
“…[25][26][27] An initial fungal colonization at a peripheral site in the first days of life may well be better managed by topical rather than systemic antifungal agents, as it mostly depends on the inefficiency of the host barrier defense. However, this treatment cannot be proposed for all of the potential sites in every preterm neonate, because it is unknown which sites will become colonized, and some sites cannot be treated topically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27] An initial fungal colonization at a peripheral site in the first days of life may well be better managed by topical rather than systemic antifungal agents, as it mostly depends on the inefficiency of the host barrier defense. However, this treatment cannot be proposed for all of the potential sites in every preterm neonate, because it is unknown which sites will become colonized, and some sites cannot be treated topically.…”
Section: Discussionmentioning
confidence: 99%
“…41 A shift toward nonalbicans species, in fact, has been noted in other high-risk patients. 25 Our data nevertheless show that the patterns of sensitivity of Candida to fluconazole remained the same during the 3-year period (as reported by Kaufman et al 42,43 ), and there was no significant increase in rate of colonization and infection by the natively resistant Candida species (C krusei and C glabrata), 22 as expressed by the crude number of their isolates in group B. "It would be surprising if antifungal prophylaxis had no effect on the pattern of pathogens causing infection in patients receiving prophylaxis," 20 but changes in this pattern do not seem related to an increased risk for colonization and infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first RCT of nystatin prophylaxis (100,000 units orally, three-times daily) was studied in ventilated preterm infants weighing under 1250 g until 1 week after they were extubated and demonstrated a decrease in Candida UTI but no effect on the incidence of fungal BSI on subanalysis [39]. Candida BSI occurred in none of the 33 nystatintreated patients compared with two of the 34 (6%) placebotreated patients (p = 0.25).…”
Section: Nystatinmentioning
confidence: 99%
“…The Cochrane review data revealed a statistically significant reduction in invasive fungal infections in infants who received prophylaxis (typical relative risk: 0.23; 95% CI: 0.11-0.46), with a number needed to treat of nine (95% CI: 6-17) [46]. Further study of nystatin prophylaxis is needed in extremely preterm infants as, thus far, there is only one RCT in infants weighing under 1250 g [39]. Epidemiologic studies including critical information regarding antifungal prophylaxis and data by each gestational age and 100 g birthweight group are needed.…”
Section: Fluconazole or Nystatin?mentioning
confidence: 99%